Urgensi Perlindungan Data Pribadi Terhadap Pengguna dan Kontak Darurat dalam Transaksi Pinjaman Online - Sinaga, Rio Alfred; Widyaningrum, Tuti (FOCUS, 2025)
Currently the financial sector is facing a new model of technology so called fin-tech. Financial technology   based   on   Peer   to   Peer   Lending   (P2PL-based   Fintech)   is   one   of   the   new   breakthroughs  in  financial  services  institutions  in  Indonesia.  The  presence  of  P2PL-based Fintech is a solution for people who have not been touched by banking but have technology literacy. However  P2PL not only give positive impact but also negative impact i.e it’s spread the  privacy  of  data  consumer  to  whom  inresponsibilty.  Therefore  it  is  need  to  give  legal  protection to consumer. The aim of this paper is to examine the legal protection of borrowers' personal data in online loan application services. The method used in this paper is a normative legal method with a statutory approach and a factual approach. The results of the study show that legal protection for consumer has in Law No. 8 of 1999 on Consumer Protection,  of 2008 OJK Regulation No. 1/POJK.07/2013 Tentang Perlindungan Konsumen Sektor Jasa Keuangan, Ministerial  Regulation  No.  20  of  2016    on  Personal  Data  Protection  within  Electronic  Systems  however these regulations has not provide data privacy however these  regulations  are deemed insufficient in preventing large-scale data breaches.